Kinerja Mesin Diesel Dengan Bahan Bakar Minyak Hasil Pirolisis Sampah Plastik - Murdieono, Agus, Nur Aklis,ST,M.Eng (2017)
Processing of plastic waste using pyrolysis method is one way to reduce the volume of plastic waste, and results from the pyrolysis of plastic waste can be used as fuel in the engine. In this study, the plastic to be used is LDPE plastic. Temperature pyrolysis process in this study of between 30-330 ° C. Pyrolysis oil waste plastic in chemical properties of the test in terms of the value of the flash point before being used as fuel for diesel engines. Flash point test method using ASTM D 93 method. Value in diesel fuel flash point is 52 °C, while the results of pyrolysis oil to be used in this study is 27 oC. In the process pungjian pyrolysis oil to diesel fuel pyrolysis oil is used as a mixture of plastic waste and main fuel is dexlite. Variations percentage of the mixture in this research is 100% dexlite, pyrolysis oil 10%: 90% dexlite, pyrolysis oil 12.5%: 87.5% dexlite. In performance testing of diesel engines using fuel oil plastic waste pyrolysis captured data is Torque, Power, Fuel Consumption and Specific Fuel Consumption Keywords : plastic waste LDPE, fuel pyrolysis, dexlite, performance diesel engine